Land-Based Learning and Indigenous Perspectives in Educational Technology (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2024)
The shift to online learning has transformed higher education but raises critical questions about integrating Indigenous ways of knowing. This paper explores the potential to bridge land-based learning with virtual classrooms, which centers relationships between Indigenous peoples and the land. While online spaces often reflect settler-colonial narratives, they also offer opportunities to amplify Indigenous voices through multimedia tools and digital collaborations.Educators can create inclusive, equitable environments by challenging misconceptions of online spaces as culturally neutral and fostering collaboration with Indigenous knowledge holders. This approach enriches learning and reimagines students’ relationships with the land, blending tradition with innovation in education.